Primary malignant melanoma of the esophagus. Issue 4 (20th April 2022) - Karapiperis, Dimitrios; Vrakas, Spyridon; Ignatova, Simone; Tribonias, George; Franzen, Thomas
Abstract: We report a case of primary malignant melanoma of the esophagus. Abstract : Primary malignant melanoma of the esophagus (PMME) is a rare primary neoplasm of the esophagus. Although it is rare, it must be borne in mind, as early and correct diagnosis could offer the patient a better prognosis.